Effect of photodynamic therapy on biofilm formation of drug-resistant Acinetobacter baumannii - ZAN Yan; HUANG Liyi; XUAN Weijun; ZHEN Xiumei; HE Lixia; YIN Xingjian (Guangxi Yike Daxue xuebao)
Objective To explore the effect of potassium iodide (KI) combined with methylene blue (MB)-mediated antimicrobial photodynamic therapy (aPDT) on the biofilm formation of multidrug-resistant Acinetobacter baumannii (MDRAb) and extensively drug-resistant Acinetobacter baumannii (XDRAb). Methods MDRAb strains and XDRAb strains were selected as experimental objects. Under the irradiation of 10 J/cm2 light energy density, sublethal aPDT was applied to MDRAb and XDRAb for different times of photodynamic intervention. The biofilm formation of drug-resistant bacteria was determined with aPDT intervention by crystal violet semiquantitative method. The effect of KI combined with MB-mediated aPDT on biofilm formation of DRAb was explored by comparing the expression levels of aPDT on MDRAb and XDRAb at different intervention times. Results Under the irradiation of 10 J/cm2 light energy density, the biofilm expression levels of MDRAb and XDRAb after multiple interventions with sublethal dose of aPDT were significantly decreased compared with those before intervention (P < 0.05), and the biofilm expression levels after intervention for seven times were significantly decreased compared with single intervention (P < 0.001). The expression level of biofilm after single intervention was not significantly decreased compared with that after four consecutive times intervention, nor was there a significant decrease when comparing four consecutive times with seven consecutive times intervention (P > 0.05). Conclusion KI combined with MB-mediated aPDT can decrease the biofilm formation ability of DRAb. Seven consecutive times intervention can significantly inhibit the biofilm formation ability of drugresistant bacteria, and reduce the biofilm formation amount of drug-resistant bacteria in vitro.